Divergent means and convergent inequality of incomes among the provinces and cities of urban China - John Knight; Li Shi; Zhao Renwei (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
Two precisely comparable national household surveys relating to 1988 and 1995 are used to analyse changes in the inequality of income in urban China. Over those seven years province mean income per capita grew rapidly but diverged across provinces, whereas intra-province income inequality grew rapidly but converged across provinces. The reasons for these trends are explored by means of various forms of decomposition analysis. Comparisons are also made between the coastal provinces and the inland provinces. The decompositions show the central role of wages, and within wages profit related bonuses, together with the immobility of labour across provinces, in explaining mean income divergence. The timing of economic reforms helps to explain the convergence of intra-province income inequality. Policy conclusions are drawn. – China ; spatial inequality ; incomes ; wages ; convergence ; divergence
Keywords: D63; I31; 330; Regionale Einkommensverteilung; China